Health literacy and chronic disease: a comparison of somatic and mental illness - Griese, Lennert; Schaeffer, Doris (Frontiers in Public Health, 2025)
BackgroundHealth literacy (HL) is increasingly recognized as essential for preventing and managing chronic illness but also for strengthening health resources and skills. However, studies on HL of people with chronic illness that adopt a multidimensional approach encompassing the three HL domains health care, disease prevention, and health promotion, remain scarce. This study aims to (a) compare HL across these three domains in individuals with chronic somatic illness, chronic mental illness and those without any chronic illness, (b) to explore where difficulties in managing health-related information occur and how these differ between groups, and (c) to analyze the relationship between demographic, social, and psychological factors and HL.MethodsData from a quantitative cross-sectional survey in Germany were stratified according to respondents with at least one chronic somatic illness, at least one chronic mental illness and without chronic illness. The survey was conducted by means of paper-assisted personal interviews. HL was measured in three domains health care, disease prevention and health promotion. Age, educational level, social status, financial resources, number of chronic illnesses, social support, and self-efficacy were included in the analysis as potential determinants of HL. Differences between groups were analyzed using bivariate statistics; multiple linear regressions were calculated to examine relationships between potential determinants and HL.ResultsRespondents with chronic mental illness showed lowest HL, followed by those with chronic somatic illness. Respondents without chronic illness achieved highest HL. This pattern was consistent across all three HL domains. Among all groups, HL was lowest in the domain of health promotion. Notable differences emerged in perceived difficulties, with respondents with mental illnesses reporting the most significant challenges. Self-efficacy and education level showed a positive association with HL across all groups, while social support was positively associated with HL among individuals with chronic mental illness. For respondents with chronic somatic illness, age was negatively associated with HL, whereas social status showed a positive association. Female respondents without chronic illness and those with chronic somatic illness demonstrated higher HL compared to male respondents.ConclusionThis study advances the understanding of HL among individuals with chronic illness and highlights the need for a greater differentiation among disease groups and HL domains in future research. Particular attention should be paid to people with chronic mental illness, whose lower HL levels increase their vulnerability.